The Key to Healthy and Radiant Skin with Balanced Nutrition - Safitri, Nurul; Cahyaningtyas, Berliana Manik Ayu; Putri, Vika Sugianto; Dewani, Locita; Nugraheni, Eti; Nugrahanti, Arifa Nayla; Saputri, Mersita Septianti; Agustin, Eny Widhia (Universitas Muhammadiyah Semarang, 2025)
Background: Skin and appearance are essential indicators of overall health and age. Nutrition plays a crucial role in supporting the skin's structure, function, and resistance to environmental stressors, highlighting the importance of a balanced diet in maintaining youthful and radiant skin.Objective: This article exposes the fundamental relationship between balanced nutrition and skin health. It emphasizes how proper nutritional intake contributes to achieving and maintaining healthy skin. This study seeks to provide actionable insights into achieving radiant and healthy skin through balanced nutrition by exploring specific nutrients and their effects on skin function.Methods: A literature review was conducted using descriptive analysis to explore the relationship between dietary habits, specific nutrients, and their impact on skin health. This method allowed the synthesis of existing research to comprehensively understand how nutrients contribute to skin elasticity, hydration, and overall skin condition.Results: Key nutrients, such as vitamins A, E, C, and omega-3 fatty acids, are essential for maintaining skin elasticity, hydration, and protection from oxidative stress. Antioxidant-rich diets are more effective at slowing aging, preventing acne, and improving skin quality. Balanced nutrition is emerging as the cornerstone of skin health and beauty. Conclusion: Healthy, radiant skin has much to do with a balanced diet enriched with essential nutrients. Fulfilling nutritional needs supports cell regeneration, protects the skin from damage, and maintains its natural balance so that it is not dependent solely on external treatments.